Smart energy and smart energy systems. (15th October 2017) - Lund, Henrik; Østergaard, Poul Alberg; Connolly, David; Mathiesen, Brian Vad
Abstract: In recent years, the terms "Smart Energy" and "Smart Energy Systems" have been used to express an approach that reaches broader than the term "Smart grid". Where Smart Grids focus primarily on the electricity sector, Smart Energy Systems take an integrated holistic focus on the inclusion of more sectors (electricity, heating, cooling, industry, buildings and transportation) and allows for the identification of more achievable and affordable solutions to the transformation into future renewable and sustainable energy solutions. This paper first makes a review of the scientific literature within the field. Thereafter it discusses the term Smart Energy Systems with regard to the issues of definition, identification of solutions, modelling, and integration of storage. The conclusion is that the Smart Energy System concept represents a scientific shift in paradigms away from single-sector thinking to a coherent energy systems understanding on how to benefit from the integration of all sectors and infrastructures. Highlights: A review of the use of Smart Energy Systems in scientific papers. The term Smart Energy Systems was first mentioned in 2009. In recent years, used mostly to express a holistic systems approach as opposed to a single sector approach. The Smart Energy Systems concept represent a radical shift in approach and understanding. The Smart Energy Systems approach has the potential to identify more efficient and affordable solutions.